The Kirov murder and Soviet history - Lenoe, Matthew E. (Matthew Edward) (New Haven [Conn.] : Yale University Press, 2010)
Drawing on hundreds of newly available, top-secret KGB and party Central Committee documents, historian Matthew E. Lenoe reexamines the 1934 assassination of Leningrad party chief Sergei Kirov. Joseph Stalin used the killing as the pretext to unleash the Great Terror that decimated the Communist elite in 1937-1938; these previously unavailable documents raise new questions about whether Stalin himself ordered the murder, a subject of speculation since 1938. The book includes translations of 125 documents from the various investigations of the Kirov murder, allowing readers to reach their own conclusions about Stalin's involvement in the assassination.
Frontmatter -- Contents -- List of Maps -- Acknowledgments -- Note on Translation, Transliteration, and Dates -- Note on Soviet Government and Territorial Structures -- Note on the Documents and Citations -- List of Acronyms and Abbreviations -- List of Archives Cited -- Introduction -- Chapter 1. From Kostrikov to Kirov, 1886-1925 -- Chapter 2. Conquering Leningrad, 1925-1929 -- Chapter 3. Kirov in Leningrad, 1930-1934 -- Chapter 4. The Scene of the Crime -- Chapter 5. Leonid Nikolaev -- Chapter 6. Nikolaev Agonistes -- Chapter 7. Stalin Responds -- Chapter 8. Fingering the Zinovievites -- Chapter 9. The Trials of the Moscow and Leningrad "Centers" -- Chapter 10. Investigating the Leningrad NKVD -- Chapter 11. The Kirov Murder and the Great Terror -- Chapter 12. Rumors, Speculation, and the Martyr Cult -- Chapter 13. The Kirov Murder in the West, 1934-1956 -- Chapter 14. The Politics of Rehabilitation and the Kirov Murder, 1953-1957 -- Chapter 15. Shatunovskaya's Investigation and After -- Conclusion -- Appendix. Biographical Sketches -- Notes -- Index of Documents -- General Index.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Kirov, Sergeĭ Mironovich, -- 1886-1934 -- Assassination; Stalin, Joseph, -- 1878-1953.; Kommunisticheskai͡a partii͡a Sovetskogo Soi͡uza -- Purges; Kirov, Sergeĭ Mironovich, -- 1886-1934; Stalin, Joseph, -- 1878-1953; Kommunisticheskai͡a partii͡a Sovetskogo Soi͡uza; Kommunističeskaja partija Sovetskogo Sojuza -- utrensningar; Political purges -- Soviet Union -- History; Political atrocities -- Soviet Union -- History; Soviet Union -- History -- 1925-1953.; Purges politiques -- URSS -- Histoire; Atrocités politiques -- URSS -- Histoire; URSS -- Histoire -- 1925-1953.; Assassination; Political atrocities; Political purges; Soviet Union; Sovjetunionen -- historia -- 1900-talet.; 1925-1953; History